1987
DOI: 10.1038/327117a0
|View full text |Cite
|
Sign up to set email alerts
|

Highly potent and selective ligands for histamine H3-receptors

Abstract: New drugs selective for histamine H3-receptors can be used to establish that these receptors are involved in the feedback control of histamine synthesis and release, and to demonstrate their distribution in the brain and peripheral tissues. These drugs provide new tools for affecting physiological and possibly pathological conditions in which histamine is involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
471
4
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 880 publications
(511 citation statements)
references
References 0 publications
34
471
4
2
Order By: Relevance
“…human when compared to rat brain slices, K i values being 16 nM (Arrang et al, 1988) and 4 nM (Arrang et al, 1987), respectively. Other functional or binding studies performed with various ligands led to even higher K i values for this compound at the hH 3 R, i.e., 85 ± 200 nM (Cheri® et al, 1992;West et al, 1999).…”
Section: Special Reportmentioning
confidence: 92%
See 2 more Smart Citations
“…human when compared to rat brain slices, K i values being 16 nM (Arrang et al, 1988) and 4 nM (Arrang et al, 1987), respectively. Other functional or binding studies performed with various ligands led to even higher K i values for this compound at the hH 3 R, i.e., 85 ± 200 nM (Cheri® et al, 1992;West et al, 1999).…”
Section: Special Reportmentioning
confidence: 92%
“…In the same way the antagonist ciproxifan displayed signi®cantly higher potency at the rH 3 R when compared to the hH 3 R in fresh brain tissues using either functional or binding assays performed under parallel conditions (Ligneau et al, 1998 and X. Ligneau, unpublished observations). Interestingly, however, both histamine and (R)a-methylhistamine were found to be nearly equipotent at the native rH 3 R and hH 3 R in brain (Arrang et al, 1987(Arrang et al, , 1988West et al, 1999). …”
Section: Special Reportmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, we reported that the selective histamine H3 antagonist thioperamide (Arrang et al, 1987) can potentiate the subjective effects of methamphetamine in rats trained to discriminate a 1.0 mg/kg intraperitoneal (i.p.) dose of methamphetamine from an i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Histamine receptors are classified into H1-, H2-and H3-receptors according to the potency order of histaminergic agonists and antagonists (Ash and Schild 1966;Black et al 1972;Durant et al 1978;Arrang et al 1983Arrang et al , 1987Schwartz et al 1986;Buschauer et al 1989). Occupancy of HI-and H2-receptors by agonists leads to the activation of phospholipase C and adenylyl cyclase, respectively (Schwartz et al 1986;Buschauer et al 1989).…”
Section: Introductionmentioning
confidence: 99%